A review on nanoparticles blended with diesel to improve combustion characteristics and reduction in emission of diesel engine. (2022) - Selvanayagam, Benjamin Franklin; A., Adarsh; K., Gowtham; S., Kavin; J., Jagan
Abstract: The thermal efficiency is increasing in combustion of diesel fuel and reducing the emission produced by the diesel fuel is the main theme of the researchers. Many researchers research and proof the bio-diesel as alternate fuel. Bio diesel is using in diesel engine performance is increasing and reducing the emission. Adding nano additives in bio diesel increase the performance and decrease the emission. Nano particles with high catalytic effect and surface area are high in chemical properties of fuel and lower emission. A review on the latest work of nano particles as a fuel additive in diesel fuel.